Recommendations for the “One Village, One Product” Strategy and Coffee Marketing Efficiency in Gowa Regency - Hasannudin, Dian Ayu Lestari; Supratman; Alam, Syamsu; Makkarennu; Hamzah, Baginda (Jurnal Hutan dan Masyarakat, 2025)
The One Village One Product (OVOP) concept seeks to raise farmers’ income by promoting regionally distinctive commodities. In Topidi Village, South Sulawesi, coffee is widely cultivated and well suited for agroforestry systems, offering high market potential. However, farmer profits are reduced by inefficient marketing channels involving many intermediaries. This study analyzed marketing institutions and the efficiency of Arabica coffee marketing using Marketing Margin, Farmer’s Share, and Profit to Cost Ratio methods. Data from four marketing outlets showed that Outlet IV, where farmers sell directly to end users, achieved the highest marketing efficiency at 44 percent for ground coffee and the highest profit. Adopting the OVOP concept for coffee could help position it as a leading regional commodity by integrating production across areas with similar landscapes, thus strengthening local industry and boosting household incomes.